Identifikasi Kepuasan Penumpang atas Implementasi Kualitas Layanan Perusahaan Penerbangan - Lianna Wijaya; Ridho Bramulya Ikhsan; Hartiwi Prabowo; Rini Kurnia Sari (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
The purpose of this study to examined the contribution of the dimensions airline service quality to build of passengers satisfaction who using LCC airlines in DKI Jakarta and identified the level satisfaction of passengers who using LCC airlines. The data collection using a questionnaire and distributed to 120 passengers who use LCC airlines in DKI Jakarta. The analysis used multiple linear regression and important-performance matrix analysis. All data is valid, reliable and the best linear unbiased estimator tests is fit. Findings showed that, simultaneously and partially, dimensions of airline service quality had a significant impact on passenger satisfaction who using LCC airlines. The results of the important-performance matrix, there are 6 attributes that require special treatments to create passenger satisfaction and only 3 attributes that are felt satisfied by passengers.